Determinant Factors of Customer Satisfaction from the SERVQUAL Perspective - Ziliwu, Randy Samadaya; Kusmiati, Eti; Wufron (Ilomata International Journal of Management, 2026)
Customer satisfaction serves as a vital benchmark for measuring a company’s performance, especially within service-based industries. Companies often encounter issues such as inconsistent service delivery and disparities between pricing and perceived value. This research has goal to measure how service quality and pricing impact client satisfaction, both individually and collectively. Utilizing a descriptive quantitative approach and a survey-based methodology, data was gathered through a census of 40 active clients of PT. ABI. The questionnaire, constructed on SERVQUAL dimensions, Zeithaml’s price perception model, and Oliver’s satisfaction theory, employed a Likert scale for measurement. Analytical techniques included validity and reliability assessments, classical assumption testing, multiple linear regression, and significance testing via SPSS software. The Research proven that service quality and pricing have significantly influence customer complacency, both partially and in tandem. The Measurement of R² value 0.704 means that these two variables explain 70.4% of the variance in satisfaction levels. The study concludes that enhancing service standards and aligning pricing with customer-perceived value can significantly improve loyalty, trust, and overall satisfaction.